If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (v + 39) + 5v = 11v + -36 Reorder the terms: (39 + v) + 5v = 11v + -36 Remove parenthesis around (39 + v) 39 + v + 5v = 11v + -36 Combine like terms: v + 5v = 6v 39 + 6v = 11v + -36 Reorder the terms: 39 + 6v = -36 + 11v Solving 39 + 6v = -36 + 11v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-11v' to each side of the equation. 39 + 6v + -11v = -36 + 11v + -11v Combine like terms: 6v + -11v = -5v 39 + -5v = -36 + 11v + -11v Combine like terms: 11v + -11v = 0 39 + -5v = -36 + 0 39 + -5v = -36 Add '-39' to each side of the equation. 39 + -39 + -5v = -36 + -39 Combine like terms: 39 + -39 = 0 0 + -5v = -36 + -39 -5v = -36 + -39 Combine like terms: -36 + -39 = -75 -5v = -75 Divide each side by '-5'. v = 15 Simplifying v = 15
| 3679.6530=171.9464*h | | 5k-12=-22 | | -4x-16=-33 | | cbrt(x)+cbrt(x-16)=cbrt(x-8) | | 1378384.64=4534.16*h | | (x-2)2+(y-4)2=36 | | g(p+3)=2x^2+5x+2 | | 9x-5=32 | | 7(x-3)=(4x+5) | | (2k-1)x^2-7x+(k+9)=0 | | 8a-28+3a=9a | | 22(x-5)+1x=-11-(x-1) | | 2a-19=7a+31 | | 6a-5a=13 | | 12p-16=-44+16p | | (p*p*p)-(1p*2p)=(p*p)+40p | | 4x^2=1764(-25x^2) | | 4x^2=1764-25x^2 | | 4x^2=-25x^2 | | 50+60+x+70=180 | | (p*p*p)-(2p*2p)=(p*p)+40p | | 4z+2+4z=10z-22 | | 5(u-8)-5=-3(-8u+9)-3u | | (6z-46)+33=5z+14 | | 3d+4(d-2)= | | x^2=7+2 | | 2x-10x-12=0 | | 4*3.14(x^2+25x+25)= | | 6t+42=7t+27 | | 5x^2+2x=175 | | 65=5+5x | | 3=2w+7 |